The Identity of Iranian Architecture and the Formation of Fashion Design Ideas - Pouria Mohammad Karimi; Cyrus Bavar (Salehan Institute of Higher Education, 2018)
Throughout history, fashion and architecture have repeated each other in terms of form and appearance. It seems quite natural that they share not only their initial function, which is to provide shelter and protect human; but also show skills in creating space and volume beyond the two-dimensional plates and materials. In recent years, the relationship between clothing design and architecture has become more significant. Computer tools and software have changed the borders of designing each one. Buildings are more fluid and clothes are more architectural. The architectural alphabet in fashion from one hand, and on the other hand the fashion ideas and methods used in architecture as well as experiencing similar themes in both domains are among the features of these arts. The exploitation of such common points among the two areas challenges the conventional ideas and pre-defined concepts of design, putting forward new solutions and experiences for designers. In this research, some of these common ideas have been studied and how these ideas are linked within both of these domains. The method of this research is descriptive and analytical; and data are collected from documents and research materials including books, articles, photos and electronic resources. This research seeks the common ideas in architecture and fashion and their mutual interaction with each other and provides some examples in both arts. The results of this research show that architecture has an effective role in shaping fashion and the attitude to the clothing design.